Validating a brief measure of four facets of social evaluation - Koch, Alex; Smith, Austin; Fiske, Susan T.; Abele, Andrea E.; Ellemers, Naomi; Yzerbyt, Vincent (Behavior Research Methods, 2024)
Five studies (N = 7972) validated a brief measure and model of four facets of social evaluation (friendliness and morality as horizontal facets; ability and assertiveness as vertical facets). Perceivers expressed their personal impressions or estimated society’s impression of different types of targets (i.e., envisioned or encountered groups or individuals) and numbers of targets (i.e., between six and 100) in the separate, items-within-target mode or the joint, targets-within-item mode. Factor analyses confirmed that a two-items-per-facet measure fit the data well and better than a four-items-per-dimension measure that captured the Big Two model (i.e., no facets, just the horizontal and vertical dimensions). As predicted, the correlation between the two horizontal facets and between the two vertical facets was higher than the correlations between any horizontal facet and any vertical facet. Perceivers’ evaluations of targets on each facet were predictors of unique and relevant behavior intentions. Perceiving a target as more friendly, moral, able, and assertive increased the likelihood of relying on the target’s loyalty, fairness, intellect, and hubris in an economic game, respectively. These results establish the external, internal, convergent, discriminant, and predictive validity of the brief measure and model of four facets of social evaluation.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Adversarial collaboration; Big Two; Brief measure; Four facets; Validity